Metode inquiry interaktif-aktif sebagai metode pengajaran dan pembelajaran Bahasa Mandarin di era digital 4.0 - Hartoko, Herisha Valentyne; Idris, Moch. Mansyur Maulana; Setiawati, Ester (2021)
This article was written with the aim of exploring the existence and dynamics of the Chinese language learning process strategy in the digital 4.0 era. Currently the world is in the digital era 4.0, various advances in information technology have an impact on changes in all aspects of people's lives, one of which is the field of education. The teaching and learning process carried out by educators and students in the digital era is different from the previous era. Changes that occur in this learning process require learning strategies that are in accordance with the development of information technology. The need for IT-based teaching and learning concepts and mechanisms cannot be avoided. The era of digitalization requires educators to have more effective strategies and methods in teaching Mandarin to make it easier for students to learn.